Rethinking prejudice?: Old debates dressed up in new clothes - Kiguwa, Peace (PINS-Psychology in Society, 2016)
BOOK REVIEW Beattie, Geoffrey (2013) Our racist heart? An exploration of unconscious prejudice in everyday life. London: Routledge. ISBN 978-0-415-61299-9 pbk. Pages ix + 295